Berinovasi Pasca Covid-19 Melalui Pengelolaan Sampah Desa Bandaran - Wahyu Maulana; Rohmaniyah Rohmaniyah (Jurnal Ilmiah Pangabdhi, 2022)
One effective way to reduce piles of waste is to manage it into innovative handicraft products. In addition to having an impact on cleanliness and health, the community also has economic value activities so that they become passive income. This year's KKN theme is "Creative and Work After the Covid 19 Pandemic", one of the work programs is to manage community waste into handicraft products that have economic value. The goal is to make the assisted villages / KKN partners become strong and independent villages after the Covid 19 pandemic. The location of this KKN is located in Bandaran Pamekasan Village. The method used is in the form of FGD, mentoring to training which is packaged in a community empowerment. The results of the service show the enthusiasm of the surrounding community in following the various stages carried out in this service so that they can create craft products in the form of ashtrays. Where this service can be useful for the community, it can also boost the economy and increase public awareness that lacks direct touch like a KKN work program like this. That way, people's creativity emerges to produce innovative products from waste.